PENGEMBANGAN E-MODUL INTERAKTIF BERBASIS LITERASI SAINS PADA MATERI IKATAN KIMIA KELAS X SMA/MA SEDERAJAT - Saragih, Eldifa Rotua; Erviyenni, Erviyenni; Rasmiwetti, Rasmiwetti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The development of an Interactive E-Module Based on ScienceLiteracy for chemical bonding material aims to produce a valid E-Module andunderstand user responses. The research employs a Research and Development (R&D)design using the ADDIE model (Analysis, Design, Development, Implementation,Evaluation), limited to the implementation stage. The data collection instruments usedwere validation sheets and user response questionnaires. The research subjects were 3students for individual trials, 2 teachers, and 20 students for limited trials from twoschools in SMAN Pekanbaru. The research results show that the Interactive E-ModuleBased on Science Literacy is valid based on the evaluations of material and mediavalidators, with average percentage scores of 92.64% and 91.96%, respectively. Thequestionnaire results from teachers and students fall into the excellent criteria, withaverage percentage scores of 92.05% and 90.28%, respectively. Therefore, theInteractive E-Module Based on Science Literacy for chemical bonding material is validand can be used as learning materials in chemistry learning.Key Words: Interactive E-Module, Science Literacy, Chemical Bonding